INTELLECTUAL CAPITAL TERHADAP FINANCIAL PERFORMANCE DAN SUSTAINABLE GROWTH - Dian Agustia; Nur Fadjrih Asyik; Nidia Midiantari (EKUITAS (Jurnal Ekonomi dan Keuangan), 2021)
ABSTRACT   This study aims to examine the effect of intellectual capital on company financial performance and company sustainability growth. This study uses manufacturing companies listed on the Indonesia Stock Exchange in 2014-2018. This study found that the components of intellectual capital have an effect on company performance, this is because well-managed intellectual capital is the main driver of increasing company performance and is also supported by superior intellectuals that will have an impact on the company's sustainable growth. Intellectual capital which includes human capital, structural capital, and relational capital is able to improve the company's financial performance, which in turn will be able to increase investment. This investment will ultimately increase the market reaction which is reflected in the company's stock price (company value). Intellectual capital is also an impetus for companies to be able to grow sustainably, especially in terms of human capital owned by the company. Companies must continue to develop and empower their potential resources in order to advance the company so that the company can win in the competition which is getting heavier.